Language learning in higher education: portuguese student voices - Pinto, Susana (2015)
This paper begins by reviewing European language education policies in higher education and relating these to the bottom-up language provision practices currently applied in higher education institutions. The paper then focuses on a case study at the University of Aveiro (Portugal) that sets out to identify students’ social representations concerning: (i) the importance of integrating foreign language courses into their degree/master/PhD programmes and (ii) the languages they consider to be more important in their academic training and the reasons for this. The findings indicate that the vast majority of responding students consider the integration of language courses in the curricula to be relevant from a doubly pragmatic perspective. Firstly, English is seen as a pathway to employability, mobility and the accessibility of knowledge, while other foreign languages (Spanish, French and German) are viewed as ‘differentiating assets’ in the professional marketplace.